Step 4: stick or twist? A review of asthma therapy - Slater, Mariel G.; Pavord, Ian D.; Shaw, Dominick E. (BMJ Publishing Group, 2016)
Many people with asthma do not achieve disease control, despite bronchodilators and inhaled corticosteroid therapy. People with uncontrolled asthma are at higher risk of an asthma attack and death, with mortality rates estimated at 1000 deaths/ year in England and Wales. The recent National Review of Asthma Deaths (NRAD) report, ‘Why asthma still kills’, recommended that patients at step 4 or 5 of the British Thoracic Society/Scottish Intercollegiate Guidelines Network (BTS/SIGN) guidance must be referred to a specialist asthma service. This article reviews the 2014 evidence base for therapy of asthma patients at BTS/SIGN step 4 of the treatment cascade, in response to key findings of the NRAD report and lack of preferred treatment option at this step.